2019
DOI: 10.1002/bse.2327
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable consumption in China: New trends and research interests

Abstract: China is currently the largest CO2 emitter in the world and demonstrates one of the highest levels of energy consumption. The sustainable consumption behavior has increased in China, especially in urban cities. Some clear evidence of this includes food purchasing behavior. Recent studies have also suggested that considering full product information transparency, consumers are willing to pay premium prices for products. With this in mind, sustainable consumption must still be facilitated by related policies, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0
2

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(45 citation statements)
references
References 70 publications
0
36
0
2
Order By: Relevance
“…The latest studies have also indicated that considering full product information transparency, consumers are inclined to pay premium prices for goods [18] ( Shao and Ünal, 2019). In 2001, the China Consumers Association summarized the concept of green consumption as having three aims: to encourage consumers to choose green products that are beneficial to health or non-pollutive; to reasonably dispose of waste in the process of consumption, and to guide the changing concept of consumption and encourage more attention to be paid to environmental protection, resource conservation, and sustainable consumption while pursuing comfort and health [19] (Shao, 2019).…”
Section: Sustainable Apparel Consumption In Chinamentioning
confidence: 99%
See 1 more Smart Citation
“…The latest studies have also indicated that considering full product information transparency, consumers are inclined to pay premium prices for goods [18] ( Shao and Ünal, 2019). In 2001, the China Consumers Association summarized the concept of green consumption as having three aims: to encourage consumers to choose green products that are beneficial to health or non-pollutive; to reasonably dispose of waste in the process of consumption, and to guide the changing concept of consumption and encourage more attention to be paid to environmental protection, resource conservation, and sustainable consumption while pursuing comfort and health [19] (Shao, 2019).…”
Section: Sustainable Apparel Consumption In Chinamentioning
confidence: 99%
“…China is currently facing severe environmental distress, which will require a shift in the consumer culture to allow for a fair sharing of resource access within the limits imposed by the environmental boundaries. However, most consumers are not inclined to reduce their level of consumption, although they may be ready to change its composition toward sustainable consumerism [2,19] (Chi, 2015;Shao, 2019). To overcome public reservation and avoid individualism-based materialism dominating the pursuit of good living standards and the concept of the public good, a new combination of public regulation, citizenship, education, and media information will be necessary.…”
Section: Sustainable Apparel Consumption In Chinamentioning
confidence: 99%
“…Meanwhile, this assessment is meaningful to the transformation of drivers behind China's economic growth and the sound development of carbon trading market. Moreover, as the world's largest developing country and carbon‐emitting country, China plays a vital role in global carbon emissions abatement (Shao, ; Xun, ). The results in this paper will help policy makers perfect the CET system and may also promote the CET‐covered enterprises to carry out low‐carbon technology innovation to better achieve the reduction of carbon emissions in China.…”
Section: Introductionmentioning
confidence: 99%
“…Consumers could seek economic incentives or savings in products with lower tax in order to achieve a good value for money and, at the same time, to feel that they choose a fashion choice (Alonso‐Almeida, 2019). In other words, an increase of the feeling of “being the first one.” Moreover, given that today's consumers are pursuing more sustainable ways of consumption (Alonso‐Almeida et al, 2020; Shao, 2019; Venugopal & Shukla, 2019), their motivation could be reinforced.…”
Section: Literature Reviewmentioning
confidence: 99%